Visualizing glutamatergic cell bodies and synapses in Drosophila larval and adult CNS. - Daniels, R.W.; Gelfand, M.V.; Collins, C.A.; DiAntonio, A. (Journal of Comparative Neurology, 2008)
Glutamate is the major excitatory neurotransmitter in the vertebrate central nervous system (CNS) and at Drosophila neuromuscular junctions (NMJs). Although glutamate is also used as a transmitter in the Drosophila CNS, there has been no systematic description of the central glutamatergic signaling system in the fly. With the recent cloning of the Drosophila vesicular glutamate transporter (DVGLUT), it is now possible to mark many, if not all, central glutamatergic neurons and synapses. Here we present the pattern of glutamatergic synapses and cell bodies in the late larval CNS and in the adult fly brain by using an anti-DVGLUT antibody. We also introduce two new tools for studying the Drosophila glutamatergic system: a dvglut promoter fragment fused to Gal4 whose expression labels glutamatergic neurons and a green fluorescent protein (GFP)-tagged DVGLUT transgene that localizes to synapses. In the larval CNS, we find synaptic DVGLUT immunoreactivity prominent in all brain lobe neuropil compartments except for the mushroom body. Likewise in the adult CNS, glutamatergic synapses are abundant throughout all major brain structures except the mushroom body. We also find that the larval ventral nerve cord neuropil is rich in glutamatergic synapses, which are primarily located near the dorsal surface of the neuropil, segregated from the ventrally positioned cholinergic processes. This description of the glutamatergic system in Drosophila highlights the prevalence of glutamatergic neurons in the CNS and presents tools for future study and manipulation of glutamatergic transmission.